Kebijakan Strategis Peningkatan Kapasitas Pasar Tradisional Dan Pedagang Kaki Lima Dengan Konsep Kemitraan Di Tangerang Selatan - Berlianingsih Kusumawati; Muchtar Riva’i; Ali Chaerudin (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2013)
Presidential Regulation No. 112/2007 and Regulation of the Minister of Trade No. 53/2008 concerning the Arrangement and Development of Traditional Markets in Modern Market has been established. So along with the implementation of these regulations, then the rules to increase the capabilities and bargaining power of traditional traders, street vendors and entrepreneurs of modern markets is a strategic policy. The purpose of this study is to examine the concept of "partnership" among small and large enterprises. The method used socio-legal which determine and analyze power behavior/ effectiveness of the regulations require a review of the philosophical, juridical, economic, sociological and political, and examine methods follow the theory of participation by conducting a survey of objects that match the theme of this research. The result informed us that the Local Government of Tangerang Selatan has been launched the local regulation which is legally very beneficial for retail trade arrangements between traditional markets, and the Modern Market. However, the regulation has not been tested in practice as an evident effectiveness of the regulation.